1998
DOI: 10.1212/wnl.51.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Laminin α2 muscular dystrophy

Abstract: Our data suggest that the large majority of laminin alpha2-deficient patients show laminin alpha2 gene mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 11 publications
6
89
0
2
Order By: Relevance
“…In these cases, patients less severely affected presented a clinical course characterized by late-onset muscle weakness, achievement of ambulation, and a CK level below 1000 U/l, with and without neuronal migration defects in MRI (Herrmann et al 1996;Mora et al 1996;Allamand et al 1997;Naom et al 1997;Morandi et al 1999). Severe phenotypes can be induced by mutations that completely avoid expression of the protein (HelblingLeclerc et al 1995;Nissinen et al 1996;Pegoraro et al 1996;Guicheney et al 1998;Pegoraro et al 1998); milder CMD phenotypes have been observed in patients with mutations that induce production of a reduced amount of normal protein or expression of a partially functional protein (Allamand et al 1997;Naom et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, patients less severely affected presented a clinical course characterized by late-onset muscle weakness, achievement of ambulation, and a CK level below 1000 U/l, with and without neuronal migration defects in MRI (Herrmann et al 1996;Mora et al 1996;Allamand et al 1997;Naom et al 1997;Morandi et al 1999). Severe phenotypes can be induced by mutations that completely avoid expression of the protein (HelblingLeclerc et al 1995;Nissinen et al 1996;Pegoraro et al 1996;Guicheney et al 1998;Pegoraro et al 1998); milder CMD phenotypes have been observed in patients with mutations that induce production of a reduced amount of normal protein or expression of a partially functional protein (Allamand et al 1997;Naom et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the severe phenotype is caused by mutations that drastically affect the expression of LAMA2 or the structure of the protein (Nissinen et al 1996;Pegoraro et al 1996;Guichenney et al 1998;Pegoraro et al 1998). On the other hand, a wide range of milder phenotypes in CMD patients are caused by partial merosin deficiency, which can be produced by an in-frame deletion in LAMA2 (Allamand et al 1997), or mutations that permit production of a partially functional protein or a reduced amount of normal protein (Naom et al 1998(Naom et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…lAMA 2 mutations are markedly variable spanning all protein domains [92][93][94] and, in general, the molecular diagnosis is not considered a priority in children with MDC1A, due to the homogeneous phenotype, the easy immunohistochemical analysis of laminin alpha-2 chain in muscle 1,2,60 and skin 95 , and the characteristic white matter abnormalities on neuroimaging. however, siala et al 96,97 have emphasized the utility of mrNA analysis in cases of MDC 1A to understand the mechanism of the mutation and the genotype-phenotype correlation.…”
Section: Merosin-deficient Congenital Muscular Dystrophy: Mdc1amentioning
confidence: 99%
“…2,5,10 Analysis of the laminin a2 chain cDNA or the LAMA2 gene itself showed that nucleotide substitutions, small deletions, or insertions induce complete merosin deficiency. Most of the mutations are localised in the N-terminal domain (exons 1 ± 31) and are predicted to produce truncated proteins.…”
Section: Mutationsmentioning
confidence: 99%
“…A 2 bp deletion, 2098delAC (703X), has been repeatedly found in several studies. 2,5,10 A nonsense mutation, C967X, has also been identified in several Italian families. Some larger deletions have been reported.…”
Section: Mutationsmentioning
confidence: 99%